Criminal law policy in the field of fair competition protection and competition policy: correlation and problems of interdependence - Danilovskaia, Anna (Юридические исследования, 2023)
The subject of the study is the criminal law policy in the field of fair competition protection and competition policy, certain aspects of their correlation and problems of implementation, including the state of legislation and law enforcement. The purpose of the work is to identify the problems of interdependence of regulatory, protective, including repressive directions of state policy in the field of competition protection and to identify ways to solve them. The research methodology is based on general scientific and private scientific methods of cognition - system analysis, logical, comparative, formal dogmatic, historical and legal methods, statistical methods, questionnaires, legal forecasting. The work resulted in conclusions on the interdependence of competition and criminal law policy in the field of competition protection, proposals for improving the diversified mechanism for countering encroachments on fair competition. Scope of application of the results: legislative, scientific, educational activities. The novelty of the study is: 1) in the features of the conducted analysis of the statistics of anticompetitive violations, which is based on the author's study of sentences imposed in relation to crimes whose compositions have signs of violations of antimonopoly legislation; 2) in establishing the preventive and suppressive significance of the Federal Law "On Protection of Competition" in relation to anticompetitive crime, as an element of competition policy relevant to criminal law 3) in proposals to strengthen the preventive significance of a special law, improve the norms of criminal legislation, as well as the mechanism of interaction between antimonopoly and law enforcement agencies. The conclusions are that the criminal law policy in the field of competition protection depends on the directions of competition policy. The solution of the problems of interdependence should be aimed at strengthening the preventive meaning of a special law, clarifying the terms used to determine the grounds of criminal liability, criteria for differentiation of responsibility, as well as at eliminating gaps in the necessary criminal law repression, normative consolidation of the interaction of antimonopoly and law enforcement agencies.